2009
DOI: 10.1007/s00425-009-1091-3
|View full text |Cite
|
Sign up to set email alerts
|

Precocious pollen germination in Arabidopsis plants with altered callose deposition during microsporogenesis

Abstract: Pollination is essential for seed reproduction and for exchanges of genetic information between individual plants. In angiosperms, mature pollen grains released from dehisced anthers are transferred to the stigma where they become hydrated and begin to germinate. Pollen grains of wild-type Arabidopsis thaliana do not germinate inside the anther under normal growth conditions. We report two Arabidopsis lines that produced pollen grains able to in situ precociously germinate inside the anther. One of them was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Early studies reported the absence of CaMV 35S promoter activity in mature Arabidopsis pollen or during pollen development (Wilkinson et al, 1997;Custers et al, 1999) that were later corroborated by studies unsuccessfully using the CaMV 35S promoter to complement Arabidopsis mutants defective in pollen development (Harrison-Lowe and Olsen, 2008), induce a pollen-lethal phenotype (Zhang et al, 2009), or label pollen peroxisomes with a GFP reporter gene fusion (Footitt et al, 2007). However, other studies suggest some activity of the CaMV 35S promoter during pollen maturation in Arabidopsis because pollen callose deposition can be altered by overexpressing callose synthase5 (Xie et al, 2010) or male sterility can be induced by expressing an RNA interference construct hampering meiosis (Wang et al, 2012). Low activity or even inactivity of the CaMV 35S promoter may also be the reason for the fact that we could isolate viable and fully fertile amiR-cpgi plants because the amiRNA would not be sufficiently expressed during cPGI-critical stages of plant development.…”
Section: Discussionmentioning
confidence: 74%
“…Early studies reported the absence of CaMV 35S promoter activity in mature Arabidopsis pollen or during pollen development (Wilkinson et al, 1997;Custers et al, 1999) that were later corroborated by studies unsuccessfully using the CaMV 35S promoter to complement Arabidopsis mutants defective in pollen development (Harrison-Lowe and Olsen, 2008), induce a pollen-lethal phenotype (Zhang et al, 2009), or label pollen peroxisomes with a GFP reporter gene fusion (Footitt et al, 2007). However, other studies suggest some activity of the CaMV 35S promoter during pollen maturation in Arabidopsis because pollen callose deposition can be altered by overexpressing callose synthase5 (Xie et al, 2010) or male sterility can be induced by expressing an RNA interference construct hampering meiosis (Wang et al, 2012). Low activity or even inactivity of the CaMV 35S promoter may also be the reason for the fact that we could isolate viable and fully fertile amiR-cpgi plants because the amiRNA would not be sufficiently expressed during cPGI-critical stages of plant development.…”
Section: Discussionmentioning
confidence: 74%
“…1J), indicating that 5PT12 deficiency resulted in precocious pollen germination within the anther. This is a very interesting finding, because, in Arabidopsis, only two mutants (raring-to-go and callose synthase 9) and one transgenic line overexpressing callose synthase 5 have been reported so far to show a similar phenotype with unknown mechanism (Johnson and McCormick, 2001;Xie et al, 2010).…”
Section: Deficiency Of 5pt12 Results In Precocious Pollen Germinationmentioning
confidence: 80%
“…The mechanism controlling seed dormancy is very likely to be similar to pollen dormancy and thereby 5PTs may be applied to alter seed dormancy. Recently, two lines with altered expression of callose synthases were reported to show precocious pollen germination, but at a very low incidence (4-8%) (Xie et al, 2010). However, in contrast to the 5pt12 mutant, all the reported lines, including rtg mutant, have abnormal pollen development as early as the bi-cellular stage.…”
Section: Biological Significance and Engineering Prospect Of Precociomentioning
confidence: 99%
“…Further research revealed asymmetric meiosis in the microspores of the gsl10 mutant. 31,32 GSL8 and GSL10 are each essential for microspore development and plant growth; gsl8 and gsl10 mutant plants exhibit asymmetric microspore meiosis and dwarfism. 33 A atgsl8 mutant, unlike other gsl8 mutants, which are seedling lethal, produces tetraploid meiocytes through random premeiotic endomitosis due to a defect in cell wall formation caused by defective callose deposition.…”
Section: Callose Biosynthesis During Male Reproductive Development Inmentioning
confidence: 99%